Digital Fluency as a Missing Mechanism in Government Digital Transformation: Linking Digital Literacy, Technostress, and Employee Performance - Bertilia Utari; Faurani Santi Singagerda (FEB - Universitas Lampung, 2026)
This study examines the effects of digital literacy and technostress on employee performance through digital fluency among Indonesian civil servants implementing the Electronic-Based Government System (SPBE). Drawing on Dynamic Capabilities Theory, it proposes that digital literacy enhances digital fluency and performance, while technostress reduces both outcomes, with digital fluency serving as a mediating mechanism. A quantitative cross-sectional design was employed using survey data from 252 civil servants selected through purposive sampling. Data were collected between February and April 2026 through online questionnaires and analyzed using PROCESS Macro Model 4 in SPSS with 5,000 bootstrap resamples. Measurement validity and reliability were confirmed, and Spearman correlation was applied due to non-normal data distribution. Results indicate that digital literacy significantly improves digital fluency and employee performance, whereas technostress significantly reduces digital fluency but does not directly affect performance. Digital fluency partially mediates the relationship between digital literacy and performance and fully mediates the relationship between technostress and performance. The findings suggest that performance in digital government environments depends largely on employees’ ability to convert digital skills into digital fluency. Organizations should therefore prioritize digital fluency development and technostress reduction through targeted training and improved system design.